Philosophy of Semiotics in Samuel Beckett’s Endgame: Peircean reading - Alhelal, Ahmed Rahi; Jawad, Mustafa Talib (International Journal of Psychosocial Rehabilitation, 2020)
Since this paper concentrates on some samples of the objects used in Samuel Beckett’s Endgame (1958), the semiotics theory proposed by C.S. Peirce (1839-1914) has been applied on Beckett’s play. The play contains crucial elements that helped apply Peirce’s philosophy. Adequately, it contains objects functioned in the text of the play like "windows, armchair, ashbins ..etc". These chosen objects contributed widely to support the concept that objects are signs which referred to specific orders regarding Peirce’s writings about semiotics. This paper presented how the objects have been employed in the play act as symbols or signs rather than being objects only. The signs refer to specific notions. For example, the two small windows contained within the play and their functions in the play. It also shows how they can be interpreted relying on piece’s philosophy. These objects are clarified and interpreted depending on the acts of the characters and their speech in the play. Since the objects in the play are significant, the two windows are interpreted as the eyes of the blind character Hamm and his servant Clov. Through the windows, Clov several times looked and checked the world outside the place that they were in as if they were waiting for something to take place or someone to come. The combination of the crucial objects in the play are analyzed and clarified according to the Samuel Beckett’s Endgame and Peirce’s philosophy, and what they could mean; just like the armchair and the bins in which Hamm’s parents were placed.